AN OBSERVATION OF CLASSROOM PRACTICES IN TEACHING SPEAKING BASED ON THE 2013 CURRICULUM - Bilitoni, Jolly Fitrah (2015)
This study investigates teachers' competence in teaching speaking in classroom practices based on the 2013 curriculum. This study also aims to find out teachers' problems and responses in teaching speaking based on the 2013 curriculum. This study uses a descriptive research design employing the characteristics of a case study. The data were obtained from several sources, including classroom observations over three weeks, in which the researcher acted as non-participant observer, collection of teachers' lesson plan, and interview with teachers at the end of the process of data collection. The findings show that one of two teachers being observed have the competence in teaching speaking based on the 2013 curriculum. Moreover, the interview data show that the teachers' have several problems in applying 2013 curriculum in teaching speaking. Keywords: Teaching Speaking, 2013 Curriculum, Classroom Practices. Penelitian ini menyelidiki kompetensi guru dalam praktik-praktik pengajaran speaking di kelas berdasarkan kurikulum 2013. Penelitian ini juga bermaksud untuk mengetahui masalah-masalah dan tanggapan-tanggapan guru dalam pengajaran speaking berdasarkan kurikulum 2013. Penelitian ini menggunakan desain penelitian deskriptif yang menggunakan karakteristik dari studi kasus. Data didapatkan dari beberapa sumber, termasuk observasi kelas selama lebih dari tiga minggu dimana peneliti bertindak sebagai non-participant observer, RPP, dan wawancara dengan guru sebagai proses akhir pengumpulan data. Temuan dalam penelitian ini menunjukan bahwa satu dari 2 guru yang di observasi memiliki kompetensi dalam mengajar speaking berdasarkan kurikulum 2013. Selain itu, data dari wawancara menunjukan bahwa guru-guru mendapatkan beberapa masalah dalam mengaplikasikan kurikulum 2013 dalam pengajaran speaking. Kata Kunci: Pengajaran speaking, kurikulum 2013, praktik-praktik kelas.